Mahârah al-Kitâbah Learning Through Mind Mapping Strategies - Najah, Zughrofiyatun; Maulana, Azzah Saniyyah (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2019)
Maharah Al-Kitabah or Writing skill is one of the highest literacy skills or abilities in Arabic learning. In this way, it is important to apply Mind Mapping strategies as an alternative to Maharah Al-Kitabah learning. The purpose of this study was to see an increase in Maharah Al-Kitabah learning through Mind Mapping strategy. The study was conducted using Classroom Action Research (CAR). The researcher acts as an observer. The research subjects involved 28 students and one Arabic subject teacher as a source of research. Data collection techniques used interviews, observation, tests, and questionnaires. While the data analysis technique used a mix method that is qualitative and quantitative. Qualitative data obtained through observation, and quantitative data obtained from the results of pre-test and post-test students. The results showed that based on the results of research by observers obtained 83.3% data, observations by teachers amounted to 87.7%. Furthermore, it was concluded that the results of maharat al-kitabah learning research through Mind Mapping strategy experienced an increase, with a percentage of 8.1%. It showed that the application of Mind Mapping strategy is very necessary to improve Arabic learning, especially in the proficiency of Mahârah Al-Kitâbah. This study drawn that Mind Mapping strategy can be used as  one of  the overcoming student’s language problems in non-linguistic aspects in the form of students' interests, motivations, critical abilities, and creativity. Therefore Mind Mapping strategy is an effective strategies to improve the student’s writing learning interest and learning student’s outcome.